Surge arrester modeling using Micro-Cap - Троценко, Євгеній Олександрович; Бржезицький, Володимир Олександрович; Маслюченко, Ігор Миколайович (Technology audit and production reserves, 2016)
In this paper the results of circuit simulation of metal-oxide surge arrester using the Micro-Cap evaluation version are presented. Nowadays a surge arrester is the most common type of overvoltage protection device and appropriate modeling of such power system’s component is a significant task. Moreover, metal-oxide arresters have dynamic characteristics that are significant for studies involving lightning and other steep-front surges. Two methods of metal-oxide surge arrester modeling are described. The main innovation introduced by the paper lays in the usage of analog behavioral voltage-controlled current source and current-controlled voltage source for non-linear varistor modeling. The residual voltage test results obtained by the manufacturers were compared with the results of simulations performed with the Micro-Cap evaluation version. Both proposed models fits with a high accuracy the arrester performances reported in the data sheet. Two different lightning current waveforms were used. One of them has its first derivative equal to zero at the initial moment of time and other one does not. For both waveforms maximal residual voltages obtained in the simulation are almost equal. Effectiveness and simplicity of use make the proposed way of modeling a useful tool for insulation coordination and lightning protection studies.